Comparison of sublingual therapeutic vaccine with antibiotics for the prophylaxis of recurrent urinary tract infections - Lorenzo-Gómez, María F.; Padilla-Fernández, Bárbara; García-Cenador, María B.; Virseda-Rodríguez, Álvaro J.; Martín-García, Isidoro; Sánchez-Escudero, Alfonso; Vicente-Arroyo, Manuel J.; Mirón-Canelo, José A. (Frontiers in Cellular and Infection Microbiology, 2015)
Objective: To evaluate the clinical impact of the prophylactic treatment with sublingual immunostimulation in the prevention of recurrent urinary tract infections (rUTIs) compared with the use of antibiotics. Material and Methods: Retrospective cohort study evaluating the clinical records of 669 women with rUTIs; 339 had a 6-month prophylaxis with antibiotics and 360 had a 3-month prophylaxis with a sublingual bacterial preparation (MV 140-Uromune®). The time after the prophylaxis-period until the appearance of a new infection (assessed by uroculture) was scored during one year. Absolute risk reduction (ARR) and number needed to treat (NNT) were also calculated. Results: All patients (100%) treated with antibiotics experienced a new UTI during the scoring period of 12 months, being the mean time free of UTI 29 (±38) days. In the group treated with the bacterial preparation, only 35 (9.7%) patients experienced UTI in the same period. Kaplan-Meier curves comparing the accumulated survival (disease-free time) between both groups were significant (P < 0.0001). ARR was 90.28 % (87.18-93.38) and NNT 1.1 (1.1-1.1). Conclusions: These results suggest that the treatment with the bacterial preparation reduces rUTIs very effectively, arising as an effective strategy to reduce the frequency of rUTIs. It reduces antibiotic consumption, matching the current recommendations due to the raise of antimicrobial resistance. Randomized, double-blind and placebo-controlled, clinical trials are needed to establish more accurately the clinical impact of this bacterial preparation in patients with rUTIs.